2022
DOI: 10.1002/ctm2.947
|View full text |Cite
|
Sign up to set email alerts
|

Integrated microbiome, metabolome, and proteome analysis identifies a novel interplay among commensal bacteria, metabolites and candidate targets in non‐small cell lung cancer

Abstract: Prevotella, Gemmiger, and Roseburia were significantly upregulated at the genus level in NSCLC patients.• Nervonic acid/all-trans-retinoic acid was negatively related to Prevotella.• CRP, LBP, and CD14 were identified as potential biomarkers for NSCLC.• Transplantation of faecal microbiota from patients with NSCLC or Prevotella copri-colonized recipient mice caused inflammation and immune dysregulation in Lewis lung cancer (LLC) cells-bearing C57BL/6 mice.• Nervonic acid/all-trans-retinoic acid improved the Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 63 publications
(123 reference statements)
2
17
2
Order By: Relevance
“…An increasing body of evidence suggests that gut dysbiosis can cause immune dysregulation and chronic inflammation and even promote the progression of various tumors, including LC, through the 'gut-lung' axis (Wang et al, 2020;Ge et al, 2021;Zhao et al, 2021). Our study showed a lower proportion of Firmicutes and a higher proportion of Proteobacteria and Actinobacteriota in LC patients, which is inconsistent with the results reported by Qian et al (2022) (Figure 1B). Overall, we found differences in the composition of the gut micro-biome between the LC patients and the HC group, characterized by loss of probiotics and overgrowth of potentially pathogenic bacteria.Interestingly, the ratio of Firmicutes to Bacteroidetes (FBR) has been used as an indicator of metabolism, nutrition and evaluation of gut micro-biome in cancer patients (Xi et al, 2022).…”
Section: Discussioncontrasting
confidence: 97%
“…An increasing body of evidence suggests that gut dysbiosis can cause immune dysregulation and chronic inflammation and even promote the progression of various tumors, including LC, through the 'gut-lung' axis (Wang et al, 2020;Ge et al, 2021;Zhao et al, 2021). Our study showed a lower proportion of Firmicutes and a higher proportion of Proteobacteria and Actinobacteriota in LC patients, which is inconsistent with the results reported by Qian et al (2022) (Figure 1B). Overall, we found differences in the composition of the gut micro-biome between the LC patients and the HC group, characterized by loss of probiotics and overgrowth of potentially pathogenic bacteria.Interestingly, the ratio of Firmicutes to Bacteroidetes (FBR) has been used as an indicator of metabolism, nutrition and evaluation of gut micro-biome in cancer patients (Xi et al, 2022).…”
Section: Discussioncontrasting
confidence: 97%
“…Prevotella copri is the most well-known of the Prevotella genus and is positively correlated with many inflammatory diseases, such as rheumatoid arthritis and ankylosing spondylitis ( Tett et al., 2021 ). Transplantation of Prevotella copri induces dysbiosis of inflammatory and immune functions and can induce arthritis in mice ( Maeda et al., 2016 ; Qian et al., 2022 ). Although less well studied, Clostridium ramosum has been proven to be positively correlated with Covid-19 disease severity, as well as infection and bacteremia ( Zuo et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Disorders of gut microbiota-host co-metabolites are associated with diseases ( Yang et al., 2019 ; Yan et al., 2022 ; Qian et al., 2022 ). Correlation analysis has shown a positive correlation between the pyruvic acid and the severity of ICH.…”
Section: Discussionmentioning
confidence: 99%